Solidaritas Allah Ditengah Penderitaan Seorang Ibu Karena Kematian Anaknya: Sebuah Pendampingan Pastoral - Aritonang, Donna (Institut Agama Kristen Negeri Palangka Raya, 2023)
Death is something that no one can avoid. When parents are faced with the death of their child, it is often the mother who seems to be devastated and feels deep suffering. For this reason, this research discusses God's Solidarity in the midst of a mother's suffering due to the death of her child: an offer of Pastoral assistance. The approach used in this study is a qualitative approach by collecting data through interviews with 3 mothers who have suffered because of the death of their child and also from books, the Bible, and electronic journals that are relevant to the theme discussed. The purpose of this research is to further explore the meaning of God's solidarity in the midst of a mother's suffering as a result of the death of her beloved child as well as to become an offer of pastoral assistance for the church by paying attention to aspects of holistic or comprehensive service covering physical, mental and psychological, social and spiritual aspects so that they can provide reinforcement for every mother who experienced something similar.